Identifikasi komponen volatil asap cair daun tembakau (Nicatiana tabacum L) rajangan Identification of volatile compound of liquid smoke from tobacco leaf (Nicotiana tabacum L.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Tobacco smoke contains both a particulat and gaseous phase. Many compounds associated with tobacco smoke are known to cause certain health risks i.e